Fabrication Of An Electronic Nose And Its Application For The Verification Of Eurycoma Longifolia Extracts - Islam, Akm Shafiqul (2007)
An electronic nose based on a quartz crystal microbalance array sensor using ethyl cellulose (EC), lipids «dioetyl phosphate (DOP). triaetyl methyl ammonium chloride (TOMA), oleyl amine (OAm» and gas chromatography (GC) stationary phase materials «Apiezon